Corpos, gêneros e sexualidades na formação docente: uma intervenção artístico-pedagógica em escolas de Uberlândia-MG - Flôres, Leonardo Silva (2023)
This research deals with the creation and application of an artistic-pedagogical intervention in two schools in the city of Uberlândia (MG). The objective was to contribute to and for the continued training of teachers in Brazilian public basic education. The intervention sought to encourage the debate about gender identities and sexual orientations in classrooms, including their specificities. As a guiding question we have the following problematization: How does the teacher perceive his/her training, the education system, the social and political context for the dialogical practices about the themes of gender and sexualities with the student? This questioning reflects my perception as a gay student and teacher about micro violence and the lack of dialogue on the part of teaching staff and school managers about the debate on bodies, genders and sexualities in the classroom. The research methodology followed a qualitative approach, bibliographical review and the creation of an artistic-pedagogical intervention plan, with a performance as an integral part, which was developed and executed by me as trigger material, in order to propose an initial dialogue about the theme presented. For the theoretical foundation, we discussed the productions of teachers, researchers and artists who also corroborate studies on bodies, genders and sexualities. With the artistic-pedagogical intervention, the teaching staff of schools were invited to reflect on the need and resignification of concepts and prejudices that involve the cultural constructions about bodies and their manifestations in genders and identities, contributing to the discovery of new pedagogical paths, methodological and didactic in everyday school life in the classroom.